2021
DOI: 10.3390/atmos12111418
|View full text |Cite
|
Sign up to set email alerts
|

Control of Airborne Microorganisms by Essential Oils Released by VaxiPod

Abstract: Currently, due to the global pandemic caused by severe acute respiratory syndrome coronavirus SARS-CoV-2, new procedures and devices for effective disinfection of indoor air are of obvious interest. Various studies demonstrated quite broad ranges of the efficiency of essential oils in the control of biological aerosols. This project reports the results of investigation of the antimicrobial activity of essential oils natural for Australia (tea tree oil, eucalyptus oil and lemon myrtle) distributed by newly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…EOs, already proposed for the treatment of human infections including cystitis, could also be evaluated in veterinary medicine and could represent an important natural alternative for the development not only of functional biomaterial, such as antimicrobial nanomaterials for catheters, but also of disinfectant and other medical devices [ 32 ]. Moreover, a study conducted by Mirskaya and Agranovski [ 33 ] demonstrated a quite broad range of efficiency of EOs in the control of biological aerosols, highlighting their potential use as new procedures and devices for the effective disinfection of surfaces and indoor air.…”
Section: Discussionmentioning
confidence: 99%
“…EOs, already proposed for the treatment of human infections including cystitis, could also be evaluated in veterinary medicine and could represent an important natural alternative for the development not only of functional biomaterial, such as antimicrobial nanomaterials for catheters, but also of disinfectant and other medical devices [ 32 ]. Moreover, a study conducted by Mirskaya and Agranovski [ 33 ] demonstrated a quite broad range of efficiency of EOs in the control of biological aerosols, highlighting their potential use as new procedures and devices for the effective disinfection of surfaces and indoor air.…”
Section: Discussionmentioning
confidence: 99%
“…In the global pandemic situation, the prevention of pathogenic microbes in indoor air spaces and on various surfaces attract significant attention. Recently, as interest in disinfection methods or antibacterial materials increases, interest in antibacterial materials as natural disinfectants is also increasing [1]. The disinfectants should not only be effective in reducing the microbes present in the air but should also not be toxic to humans, allowing their continuous application [2].…”
Section: Introductionmentioning
confidence: 99%